The k-error Linear Complexity Distribution for Periodic Sequences - Zhou, Jianqin (Curtin University, 2017)
This thesis proposes various novel approaches for studying the k-error linear complexity distribution of periodic binary sequences for k > 2, and the second descent point and beyond of k-error linear complexity critical error points. We present a new tool called Cube Theory. Based on Games-Chan algorithm and the cube theory, a constructive approach is presented to construct periodic sequences with the given k-error linear complexity profile. All examples are verified by computer programs.